Ralstonia mannitolilytica bacteremia in a maintenance hemodialysis patient - Subramanian, Sreevidya; Rajkumar, S Venkatesh; Thirunarayan, M A; Samal, Debashree (Eastern Journal of Medical Sciences, 2016)
Ralstonia mannitolilytica is a nonfermentative, Gram-negative bacterium isolated infrequently from clinical samples. It is widely distributed in nature, being a frequent contaminant in water supplies. It is increasingly identified as an opportunistic pathogen in nosocomial infections, especially among immunosuppressed patients. It has also been implicated in common source nosocomial infection outbreaks due to the addition of contaminated water to parenteral fluids and to medical equipment presumed to be sterile. True bacteremia with the organism, however, cannot be ruled out, especially if it is isolated repeatedly from the same patient within 3 successive days from blood cultures. A 22-year-old Ethiopian male presented to us in December 2015 with fever with chills and rigor, vomiting, and headache. He was a known end-stage renal disease patient on thrice per week hemodialysis through a tunneled hemodialysis catheter for the past 1 year. He had an episode of catheter-related blood stream infection in October-November 2015 and was treated at a multispeciality hospital with parenteral antibiotics (piperacillin-tazobactam) for 2 weeks (for growth of Pseudomonas aeruginosa in blood cultures) during the same admission phase. The tunneled catheter was not removed then and lock therapy was used and the patient improved gradually with antibiotics. During the current admission, three blood culture sets (aerobic and anaerobic), one set from the dialysis line and two from the peripheral lines were submitted to microbiology laboratory. Blood cultures (one bottle from each of the three sets) flagged positive. The blood culture sent from the hemodialysis line was the first to flag positive 12 h after it was loaded onto the BACTEC 9050 system. This was followed by the aerobic and anaerobic bottles from the peripheral lines. The preliminary Gram-stain showed Gram-negative bacilli and the cultures grew Gram-negative organisms. The organism was identified as R. mannitolilytica by the Vitek 2C. Disc diffusion (CLSI, 2015) was done for the various antibiotics, and there was a 6 mm resistant zone for the following panel tested: Gentamicin, cotrimoxazole, aztreonam, amikacin, ceftriaxone, cefotaxime, cefepime, ceftazidime, and carbapenems; the organism was intermediate to piperacillin-tazobactam (17 mm) and was sensitive to and cefoperazone-sulbactum (23 mm). In our set up, this was the first case of R. mannitolilytica isolated as a significant pathogen in a case of true bacteremia. R. mannitolilytica can thus cause true bacteremia as well in addition to just being an environmental contaminant. Early recognition of the infection helps in instituting appropriate antibiotic with complete resolution of the infection. In our case report, the prompt report of microbiology department enabled us to treat the patient on time with appropriate antibiotic and also prevented the premature removal of the tunneled catheter. The problems caused by this bacterium occur rapidly and disease progression is fast; therefore, R. mannitolilytica infections should draw sufficient attention from clinical physicians and bacteriology workers to respond to the resulting severe consequences.